IMPLEMENTASI PEMBELAJARAN BERBASIS TEMATIK PADA PROGRAM STUDI PENDIDIKAN GURU MADRASAH IBTIDAIYAH FAKULTAS TARBIYAH UNIVERSITAS HASYIM ASY’ARI TEBUIRENG - Hosna, Rofiatul; Mahsun, Ali; Dahlan, Encep (Al Tadib : Jurnal Ilmu Pendidikan, 2015)
This study examines and answers three problems: (1)processes, (2) implementation, and (3) factors inhibiting/supportingthe implementation of the thematic learning in PGMI department ofthe faculty of UNHASY Tebuireng. By applying qualitativedescriptive method, the research team tried to explore the data to findanswers to the focus lifted. Results of this research are, (1) theprocess of learning at PGMI Department of Tarbiyah FacultyUNHASY Tebuireng Jombang before implementation of thematicbasedlearning has not been determined based on the kind of skillsthat theme; lack of election materials research, competence standard,basic competence and indicator; undetermined sub-skills-basedtheme; and yet the formulation of indicators of learning outcomes,(2) implementation of the thematic-based learning in PGMIDepartment of Tarbiyah Faculty UNHASY Tebuireng Jombang hascontained provisions kinds of subjects and types of skills that arecombined; and (3) Factors supporting the implementation of thethematic-based learning in PGMI Department of Tarbiyah FacultyUNHASY Tebuireng is easily understood by students due to thelearning process fun; more emphasis on talents, interests and needs ofstudents; students have direct experience, while inhibiting factor isthe mastery of the faculty in understanding the learning materialthematic, meaning less master lecturers in depth elaboration onthematic learning themes that will find it difficult to associate thetheme with the subject matter of each course.Keywords: Thematic Learning1 Dosen Fakultas Tarbiyah Universitas Hasyim Asy’ari Tebuireng